2006
DOI: 10.1038/sj.eye.6702265
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Triamcinolone acetonide (TA)-assisted pars plana vitrectomy in macular hole surgery

Abstract: Aim To evaluate whether Triamcinolone acetonide (TA)-assisted pars plana vitrectomy for visualisation of posterior hyaloid during macular hole surgery has any adverse effects on macular hole closure rate and intraocular pressure (IOP). Methods Case series comparing outcomes and adverse effects in patients who had surgery for macular holes with ILM peel, with and without the use of TA-assisted vitrectomy. Results During the study period, 29 patients had vitrectomy for macular holes. In 18 patients (group 1), TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
1
17
1
2
Order By: Relevance
“…Subsequent pathology disclosed the presence of ILM in specimens after TA-assisted peeling, thereby showing that is possible to remove ILM and not just vitreous. (2,8) Since then other studies have confirmed that TA-assisted ILM removal gives good results (figure 7D) (39)(40)(41) . Compared to ICG-guided ILM removal, a noncontrolled study indicates that TA has the same closure rate with significantly better visual results with no side effects (42) .…”
Section: Triamcinolone Acetonidementioning
confidence: 82%
See 1 more Smart Citation
“…Subsequent pathology disclosed the presence of ILM in specimens after TA-assisted peeling, thereby showing that is possible to remove ILM and not just vitreous. (2,8) Since then other studies have confirmed that TA-assisted ILM removal gives good results (figure 7D) (39)(40)(41) . Compared to ICG-guided ILM removal, a noncontrolled study indicates that TA has the same closure rate with significantly better visual results with no side effects (42) .…”
Section: Triamcinolone Acetonidementioning
confidence: 82%
“…A recent study compared ILM peeling with and without the use of TA. During a mean follow-up of 7.3 months, no recurrence of the MH was observed (40) . Despite of this concern, preservative-free TA appears to be a preferred agent in chromovitrectomy (43) .…”
Section: Triamcinolone Acetonidementioning
confidence: 85%
“…As shown with previous studies of intravitreal triamcinolone, the more common complications include cataract formation and elevated intraocular pressure. However, the incidence of these complications are less than expected Sakamoto et al 2002;Chang et al 2006;Kampougeris et al 2007;Kumagai et al 2007;Ueno et al 2007;Hikichi et al 2008). Several studies have shown residual retinal TA after PPV.…”
Section: Triamcinolone During Vitrectomymentioning
confidence: 93%
“…It is well known for its anti-angiogenic and anti-fi brotic properties, which can have a benefi cial effect in the treatment of conditions commonly treated with intraocular surgery (Kampougeris et al 2007). One study objectively showed a decrease in postoperative blood-ocular barrier breakdown after TA-assisted PPV, especially for diabetic macular edema (Sakamoto et al 2002).…”
Section: Triamcinolone During Vitrectomymentioning
confidence: 99%
See 1 more Smart Citation